SSR Marker Aided Parental Polymorphic Survey for Rust Resistance in Cowpea [Vigna unguiculata (L.) Walp] - M.S.Uma , Asish, I. Edakkalathur,Shailaja Hittalamani, K.P.Viswanatha, Y.M.Somashekhar and T.E.Nagaraja (Electronic Journal of Plant Breeding, 2011)
Nine Cowpea (Vigna unguiculata) genotypes-six landraces and three cultivated varieties were selected for the study. Polymorphic survey was done by using 36 SSR primers and genetic distances among parental lines were calculated. Primers VM 1, VM 28, VM 36 and VM 68 were found to be polymorphic with two to four alleles per locus. Polymorphism percentage was 11.11. The total number of polymorphic alleles were 11 and number of alleles amplified per locus on an average was 2.75. Five primers produced heterozygous bands. Primer VM 36 produced unique band for GC-3, making it useful for marker assisted introgression studies. Nine genotypes clustered into seven groups, which showed correlation to their geographical origin and distinguished the cultivated varieties from the landraces. Dendrogram consisted of two major clusters diverged at 18.56 per cent dissimilarity level. The genotypes exhibited lower diversity at molecular level and higher diversity at phenotypic level.